Exploring drivers of litter decomposition in a greening Arctic: results from a transplant experiment across a tree-line - Parker, Thomas C.; Sanderman, Jonathan; Holden, Robert D.; Blume-Werry, Gesche; Sjögersten, Sofie; Large, David; Castro-Díaz, Miguel; Street, Lorna E.; Subke, Jens-Arne; Wookey, Philip A. (Ecological Society of America, 2018)
Decomposition of plant litter is a key control over carbon (C) storage in the soil. The biochemistry of the litter being produced, the environment in which the decomposition is taking place, and the community composition and metabolism of the decomposer organisms exert a combined influence over decomposition rates. As deciduous shrubs and trees are expanding into tundra ecosystems as a result of regional climate warming, this change in vegetation represents a change in litter input to tundra soils and a change in the environment in which litter decomposes. To test the importance of litter biochemistry and environment in determining litter mass loss, we reciprocally transplanted litter between heath (Empetrum nigrum), shrub (Betula nana) and forest (Betula pubescens) at a sub-arctic tree-line in Sweden. As expansion of shrubs and trees promotes deeper snow, we also used a snow fence experiment in a tundra heath environment to understand the importance of snow depth, relative to other factors, in the decomposition of litter. Our results show that B. pubescens and B. nana leaf litter decomposed at faster rates than E. nigrum litter across all environments, while all litter species decomposed at faster rates in the forest and shrub environments than in the tundra heath. The effect of increased snow on decomposition was minimal, leading us to conclude that microbial activity over summer in the productive forest and shrub vegetation is driving increased mass loss compared to the heath. Using B. pubescens and E. nigrum litter, we demonstrate that degradation of carbohydrate-C is a significant driver of mass loss in the forest. This pathway was less prominent in the heath, which is consistent with observations that tundra soils typically have high concentrations of ‘labile’ C. This experiment suggests that further expansion of shrubs and trees may stimulate the loss of undecomposed carbohydrate-C in the tundra.